Middle Miocene-Pleistocene Magneto-Cyclostratigraphy from IODP Site U1501 in the Northern South China Sea - Shi, Meinan; Wu, Huaichun; Ferré, Eric C.; Satolli, Sara; Fang, Qiang; Nie, Yunfeng; Qin, Yuhe; Zhang, Shihong; Yang, Tianshui; Li, Haiyan (Frontiers in Earth Science, 2022)
Site U1501 of International Ocean Discovery Program (IODP) Expedition 368 locates on a broad regional basement high in the northern margin of the South China Sea (SCS). This study refines the chronostratigraphy of the upper 160 m sedimentary succession from Hole U1501C using paleomagnetic measurements and cyclostratigraphic analysis on the Natural Gamma Radiation (NGR) data. Rock magnetic analysis displays that the magnetic signal of the sediments is mainly carried by single-domain (SD) and multi-domain (MD) magnetite. A total of 12 geomagnetic reversals are identified and correlated to the geomagnetic polarity time scale (GPTS) in Geologic Time Scale 2020 (GTS2020), combining biostratigraphic data and planktonic foraminiferal oxygen records. The Milankovitch cycles of 405-kyr long orbital eccentricity, ~100-kyr short orbital eccentricity, and obliquity cycles are identified in the NGR profile. A 15.54 Myr astronomical time scale is constructed by tuning the short eccentricity cycles filtered from the NGR profiles to the La2010 astronomical solution with the constraints of the magnetostratigraphic results, biostratigraphic age datum and planktonic foraminiferal oxygen records. This new high-resolution age model provides a new temporal constraint on the tectonic and paleoenvironmental evolution in the SCS.